Rum, sodomy, prayers, and the lash revisited Winston Churchill and social reform in the Royal Navy, 1900-1915 - Seligmann, Matthew S. 1967- (Oxford University Press, 2018)
This title is an examination of British naval social policy in the opening decades of the twentieth century, under the command of Winston Churchill. It highlights an often forgotten aspect of Churchill's career and his attempts to bring the senior service into the modern world
This edition previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Churchill, Winston / 1874-1965; Churchill, Winston -- 1874-1965; Great Britain / Royal Navy / History / 20th century; Großbritannien -- Navy; Geschichte 1911-1915; Social problems / Great Britain / History / 20th century; Naval art and science / Great Britain / History / 20th century; Sozialreform; Great Britain / History, Naval / 20th century